Ideologija kot tehnologija - Krašovec, Primož (Javnost (Ljubljana), 2017)
The article is an attempt to think ideology neither on the level of the content of thought nor on the level of discourse, but on the level of its functioning, which is - this will be the main thesis of the article - firstly, mostly undiscursive and, secondly, at least in the 21st century, technologically determined in a decisive way. In distinction to classic ideological formations of the 19th and partially 20th centuries, ideology today no longer works on the level of the relation between individual minds and dominant discourses, neither does it work as a form of subjectivation; today, ideology works on a different level and in a different way: on the level that is technologically mediated and infra-subjective. Such functioning of ideology, by taking place on the (micro)level of affects, bypasses the process of subjectivation and interpellation as well as the level on which belief, meaning, and media representations function. These changes also "reprogram" the way individuals' cognitive processes work and decisively influence education, as the traditional - linear and causal - mode of "social psyche" is being replaced by new modes of social psyche, modes adapted to new media technologies and practices.
Keywords: družbena zavest; ideologija; mediji; socialna psihologija; tehnologija